Synthesis NiFe2O4 Nanoparticles by co-Precipitation Method for Degradation of Congo Red Dye - Astri Nurmayansih; Poedji Loekitowati Hariani; Muhammad Said (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2021)
The NiFe2O4 nanoparticle was synthesized using co-precipitation method. This study done to the purpose for get the photocatalyst magnetic. The product of NiFe2O4 nanoparticles were characterized by XRD, FTIR, SEM EDS and UV DRS instrumentation. The result of characterization NiFe2O4 nanoparticles was showed a sharp intensity peak at 2θ of 35.73o. The characterization using FTIR was showed the absorption band of Ni-O metal oxide at 779.24 cm-1 and the absorption band of Fe-O metal oxide at 694.37 cm-1. Characterization using SEM-EDS showed the NiFe2O4 nanoparticles have agglomeration because the nanoparticles possess high surface energy. The composition element of NiFe2O4 nanoparticles was 47.84% O, 15.37% Fe, and 9.89% Ni. Meanwhile, the result of characterization using UV DRS was showed sharp peak intensity of wavelength at 319 nm. The band gap energy of NiFe2O4 nanoparticles with direct transition in 1.11 eV and indirect transition in 1.98 eV using Tauc method. Then, the result of photodegradation toward congo red was showed effectively at the concentration in 100 mg/L, the contact time in 25 minutes and the pH in 6 or pH 5,7 with removal effectivity was 71.104%.